PENGARUH BOIKOT PRODUK TERHADAP VOLATILITAS RETURN EMITEN UNILEVER INDONESIA TBK - Kurniawan, Fernando; Fahlevi, Muhammad Ryan (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: The Palestinian-Israeli conflict heated up in October 2023. The Assembly Regarding the Law on Support for Palestinian Fighters, Fatwa Number 83 of 2023 was issued by Indonesian Ulama. According to the fatwa, aiding Israel's aggression against Palestine is illegal, but it is mandatory to support the Palestinian independence struggle against Israeli aggression. The issuance of this Fatwa further strengthens the boycott of products affiliated with Israel by the Indonesian people. From data collection to analysis and appearance to findings, the study uses quantitative and descriptive strategy methods, which use numbers to try to provide an objective picture of a scenario. Secondary data is the type of data used in this study. The Yahoo Finance web is accessible to get daily stock statistics that serve as a secondary source of data. The purpose of this study is to ascertain how market boycotts affect return volatility. The sample of this study was 127 stock prices per day during the boycott period. Conclusions can be made based on the data collected and the results of tests conducted on the description of the problem through statistical regression.that the Product Boycott has a significant effect on the Volatility Return of Unilever Indonesia Issuers, the Company needs to continue to perform well, especially in the financial market sector. Because in the financial market sector, investors need to see information or a good image of a company before investing their funds. Recommendations for further research can examine other variables or factors that play a role in determining the volatility of issuer returns such as financial performance or macroeconomic conditions.Keywords: Boycott, Return Volatility, Unilever Indonesia, Palestinian-Israeli Conflict, Stock Price